EDUKASI TEKNIK RELAKSASI GENGGAM JARI TERHADAP PENURUNAN TEKANAN DARAH LANSIA HIPERTENSI DI DESA KEDUNGBANTENG PURWOKERTO - Astuti, Winda Eka; Siwi, Adiratna Sekar; Susanti, Indri Heri (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Hypertension, a condition in which blood pressure exceeds normal limits (above 140/90 mmHg), often occurs in elderly people and increases the risk of complications. Finger pressure and relaxation techniques are effective non-pharmacological approaches to lowering blood pressure. Community service activities start from initial preparations such as pre-surveys and approvals to providing materials such as pre-tests, post-tests, and lectures and discussions using pamphlets, powerpoints and videos. From the results of this activity, it was found that this technology was effective in lowering blood pressure in the elderly. At the first meeting, the average blood pressure decreased from 166/82.7 mmHg to 157.2/76.33 mmHg, and at the second meeting from 174.03/82.7 mmHg to 163/76.6 mmHg. Elderly people tend to struggle with some movements, especially in gripping the middle finger and little finger. This activity also produces a HAKI video which explains the finger grip relaxation technique in detail.